Re-creation of a Key Step in the Evolutionary Switch from C3 to C4 Leaf Anatomy - Wang, Peng; Khoshravesh, Roxana; Karki, Shanta; Tapia, Ronald; Balahadia, C. Paolo; Bandyopadhyay, Anindya; Quick, W. Paul; Furbank, Robert; Sage, Tammy L.; Langdale, Jane A. (Elsevier, 2017)
The C4 photosynthetic pathway accounts for ∼25% of primary productivity on the planet despite being used by only 3% of species. Because C4 plants are higher yielding than C3 plants, efforts are underway to introduce the C4 pathway into the C3 crop rice. This is an ambitious endeavor; however, the C4 pathway evolved from C3 on multiple independent occasions over the last 30 million years, and steps along the trajectory are evident in extant species. One approach toward engineering C4 rice is to recapitulate this trajectory, one of the first steps of which was a change in leaf anatomy. The transition from C3 to so-called “proto-Kranz” anatomy requires an increase in organelle volume in sheath cells surrounding leaf veins. Here we induced chloroplast and mitochondrial development in rice vascular sheath cells through constitutive expression of maize GOLDEN2-LIKE genes. Increased organelle volume was accompanied by the accumulation of photosynthetic enzymes and by increased intercellular connections. This suite of traits reflects that seen in “proto-Kranz” species, and, as such, a key step toward engineering C4 rice has been achieved